"A Voice that Would Sound All the Notes": Sound and Regeneration in Vladimir Jabotinsky's Hebrew Revivalism. - Francez, Itamar (Jewish Social Studies)
The vernacularization of Hebrew speech was an integral component of the Zionist conception of national revival. In this article I explore some of the ways in which the discourse of regeneration and the figure of the "muscle Jew" shaped ideas about the sonic component of Hebrew speech, through the case of study of Vladimir Ze'ev Jabotinsky. I show that Jabotinsky took speech, and Hebrew speech in particular, to be a potent site of regeneration, viewed as the cultivation of corporeal sensitivity to form. I trace his invention of a sonic counterpart to the muscle Jew, and demonstrate how, employing a conception of speech sounds as manifesting qualities of speakers, he constructed an ideological program for regenerative Hebrew speech that challenged the grammatical prescriptions of mainstream revivalists and included observations of and prescriptions about patterns of Hebrew speech down to the level of phonemes and phonological processes.